CHAOS, MORAL DECADENCE, AND BETRAYAL (SATIRE IN "DI TEPI KALI BEKASI" NOVEL BY PRAMOEDYA ANANTA TOER) - Rudy Gunawan; Desvian Bandarsyah; Wildan Insan Fauzi (LITERA, 2019)
Indonesian revolution in 1945-1949 is a remarkable moment for all of Indonesian people which is full of heroic spirit. Interestingly, Pramoedya portrayed the revolution moment in the novel entitled “Di Tepi Kali Bekasi” with different point of view in which he used a sarcasm style of language to depicts the conditions and deliver his critics about behaviors of people from various clusters at that time. Therefore, this current study is motivated by interest to explore how satirical narrative is used in the novel. A qualitative content analysis with context unit was employed as a research method to describe and analyze in detail the description and characteristics of satire in the novel. Specifically, a concept of satire intended in this study is sarcasm, social criticism, and irony. Based on the results of analysis, there are some satirical elements in the novel namely social chaos, public unrest, bandits and robbery, betrayal, generation conflicts, youth nationalism, and immoral behavior and corruption of the army. In addition, according to Pramoedya's view, revolution is considered as an animalistic age where the revolution of soul is more important and needed by the nation instead of the armed revolution. Due to those facts, independence remains as a fake independence where unheard voice of the periphery and moral destruction are still the main problem. Generally, it is found that the satirical root in the novel is laid on two things namely Pramoedya's direct experience as a soldier and his ideas he wants to convey in the novel.Kata Kunci: Di Tepi Kali Bekasi, novel sejarah, Pramoedya Ananta Toer, satireCHAOS, DEKANDENSI MORAL, DAN PENGKHIANATAN(Satir dalam Novel Di Tepi Kali Bekasi karya Pramoedya Ananta Toer)AbstrakRevolusi fisik 1945-1949 merupakan periode yang disakralkan dan digambarkan penuh dengan semangat kepahlawanan. Namun, Pramoedya menggambarkan revolusi Indonesia dalam novel di Tepi kali Bekasi dengan gaya bahasa satir yang berisi kritikan tajam dan ironi terhadap perilaku berbagai kalangan. Tujuan penelitian ini adalah mendeskripsikan narasi satir dalam novel Di Tepi Kali Bekasi karya Pramoedya Ananta Toer. Penelitian ini menggunakan metode analisis isi kualitatif untuk menggambarkan dan menganalisis secara detail deskripsi dan karakteristik satir dalam novel. Analisis data yang digunakan adalah unit konteks. Konsep satir yang dimaksud adalah sindiran, kritik sosial, dan ironi. Unsur satir yang terdapat dalam novel adalah kekacauan sosial (chaos), keresahan masyarakat, bandit dan rampok, pengkhianatan, konflik generasi, nasionalisme pemuda, serta perilaku amoral dan korupsi tentara. Cara pandang Pramoedya mengenai revolusi adalah revolusi sebagai zaman kebinatangan, revolusi jiwa lebih berhasil daripada revolusi bersenjata, kemerdekaan hanya kemerdekaan semu, suara kaum pinggiran, dan kehancuran moral. Akar satir dalam novel Di Tepi Kali Bekasi bertumpu pada dua hal, yaitu pengalaman langsung Pramoedya sebagai tentara dan gagasan-gagasan yang ingin disampaikannya dalam novel.Kata Kunci: Di tepi kali bekasi, novel sejarah, Pramoedya Ananta Toer, Satir